2010
DOI: 10.4028/www.scientific.net/amr.97-101.3436
|View full text |Cite
|
Sign up to set email alerts
|

A Kind of CAD/CAE Integrated Modeling Technology Based on FEATURE

Abstract: A kind of CAD/CAE integrated modeling method based on feature is proposed. Firstly, analysis features are attached to CAD model of part and standard part library is formed. Secondly, the CAD model is created using standard parts. Thirdly, geometry information of analysis features is extracted from CAD model and is reconstructed automatically under CAE environment. Finally, based on feature-based meshing and combination technique, CAE model is built quickly. A prototype software for large-scale antenna structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…These advantages bring significant financial benefits to companies. Typically, there are several main waste sources in manufacturing processes: transport, inventory, motion, waiting time, over production, over processing, defects, and ineffective production that do not meet customer requirements [57]. To eliminate the waste among these eight sources and create value, lean manufacturing uses tools and techniques such as:…”
Section: Lean Manufacturingmentioning
confidence: 99%
See 4 more Smart Citations
“…These advantages bring significant financial benefits to companies. Typically, there are several main waste sources in manufacturing processes: transport, inventory, motion, waiting time, over production, over processing, defects, and ineffective production that do not meet customer requirements [57]. To eliminate the waste among these eight sources and create value, lean manufacturing uses tools and techniques such as:…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…Early research mainly focused on the idealization of CAD models and automatic mesh generation. A workflow of the CAD/CAE integrated modeling method has been suggested by Li et al [57], as shown in Fig. 8.…”
Section: Geometry Transformation For Cad/cae Integrationmentioning
confidence: 99%
See 3 more Smart Citations